Using Wave Equation to Extract Digital Signal Features - Al-Rawashdeh, A. Y.; Al-Qadi, Z. (Engineering, Technology & Applied Science Research, 2018)
Voice signals are one of the most popular data types. They are used in various applications like security systems. In the current study a method based on wave equation was proposed, implemented and tested. This method was used for correct feature array generation. The feature array can be used as a key to identify the voice signal without any dependence on the voice signal type or size. Results indicated that the proposed method can produce a unique feature array for each voice signal. They also showed that the proposed method can be faster than other feature extraction methods.